Big Five traits as (mal)adaptive behavioral responses to harsh and unpredictable environment: further evidence for the state-dependent evolution of personality - Međedović, Janko M (Psihološka istraživanja, 2020)
State-dependent behavior models of personality predict that the fitness consequences of personality are dependent on various states; hence, personality traits may be adaptive only in certain conditions. In the present research we tested the state-dependent personality model of Big Five personality traits using harsh and unpredictable environments as the extrinsic states. The data is collected in a community sample (N=221). We extracted the fitness factor from a broader set of indicators related to reproduction and mating - it consisted of higher reproductive success, longest romantic relationship duration, and earlier age of first reproduction. The only personality trait which significantly predicted fitness was low Openness to experience. However, three interactions between environmental conditions and personality in the prediction of fitness were detected: Low Agreeableness and Extraversion decreased fitness in highly unstable environments; low Openness elevated fitness, especially in harsh environments. The data are in accordance with the previous findings regarding the relations between personality and evolutionary fitness. Furthermore, current findings suggest the that state-dependent models of personality are not only valid explanations of evolutionary forces which maintain personality variation, but that they are quite robust as well, since they can be detected in a relatively small sample of reproductively active individuals.